2016
DOI: 10.1088/1674-1056/25/11/114210
|View full text |Cite
|
Sign up to set email alerts
|

Tracking molecular structure deformation of nitrobenzene and its torsion–vibration coupling by intense pumping CARS

Abstract: The structural deformation induced by intense laser field of liquid nitrobenzene (NB) molecule, a typical molecule with restricting internal rotation, is tracked by time-and frequency-resolved coherent anti-Stokes. Raman spectroscopy (CARS) technique with an intense pump laser. The CARS spectra of liquid NB show that the NO 2 torsional mode couples with the NO 2 symmetric stretching mode, and the NB molecule undergoes ultrafast structural deformation with a relaxation time of 265 fs. The frequency of NO 2 tors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The intensity enhancement is an indication of spin-dependent scattering mechanism. [25][26][27][28][29] Porporati et al showed that Bi can take part in low wavenumber modes (up to 167 cm −1 ), the oxygen atoms are mainly involved in modes of wavenumber larger than 262 cm −1 , although Fe can participate in modes between 152 cm −1 to 262 cm −1 . [30][31][32][33][34][35] The A 1 (TO 2 ) mode symmetric at 213.5 cm −1 is a soft oxygen mode and is directly associated with the oxygen displacement vector ( ā ā ā).…”
Section: Resultsmentioning
confidence: 99%
“…The intensity enhancement is an indication of spin-dependent scattering mechanism. [25][26][27][28][29] Porporati et al showed that Bi can take part in low wavenumber modes (up to 167 cm −1 ), the oxygen atoms are mainly involved in modes of wavenumber larger than 262 cm −1 , although Fe can participate in modes between 152 cm −1 to 262 cm −1 . [30][31][32][33][34][35] The A 1 (TO 2 ) mode symmetric at 213.5 cm −1 is a soft oxygen mode and is directly associated with the oxygen displacement vector ( ā ā ā).…”
Section: Resultsmentioning
confidence: 99%
“…When the C-H stretching vibrational modes 3080 cm −1 and 3050 cm −1 are excited, their frequency difference would appear at 30 cm −1 in the FT power spectra (around zero-time), as shown in figure 2(a). The peak at 70 cm −1 is assigned to the frequency difference between phenyl ring breathing mode v CC ∼1584 cm −1 and NO 2 Another major peak of the FT power spectra is the nitro group torsion mode v torsion ∼48 cm −1 , which originates from the impulsive excitation of femtosecond laser pulses [24]. Owing to the limited spectral detection range, the low-frequency mode v torsion ∼48 cm −1 is invisible in CARS spectra and can only been tracked through FT power spectra.…”
Section: Vibrational Energy Redistribution From Phenyl Modes To Nitro...mentioning
confidence: 99%
“…Nitrobenzene is one of the typical energetic materials whose geometries and spectrum properties, isomerization and even dissociation channels have been studied theoretically and experimentally [14][15][16][17][18][19] . Recently, a new reaction channel in the …”
Section: Pacsmentioning
confidence: 99%
“…Nitrobenzene is one of the typical energetic materials whose geometries and spectrum properties, isomerizations and even dissociation channels have been studied theoretically and experimentally. [14][15][16][17][18][19] Recently, a new reaction channel in the photodissociation process of nitrobenzene was reported, suggesting a unimolecular isomerization process through a typical TS R . [20] So far, most of the previous researches have focused on the dynamic properties of the roaming systems, with certain atoms or functional groups roaming around the rest part and then dissociated or isomerized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation